Balance Impairments as Differential Markers of Dementia Disease Subtype - Mc Ardle, Ríona; Pratt, Stephanie; Buckley, Christopher; Del Din, Silvia; Galna, Brook; Thomas, Alan; Rochester, Lynn; Alcock, Lisa (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Accurately differentiating dementia subtypes, such as Alzheimer’s disease (AD) and Lewy body disease (including dementia with Lewy bodies (DLB) and Parkinson’s disease dementia (PDD)) is important to ensure appropriate management and treatment of disease. Similarities in clinical presentation create difficulties for differential diagnosis. Simple supportive markers, such as balance assessments, may be useful to the diagnostic toolkit. This study aimed to identify differences in balance impairments between different dementia disease subtypes and normal ageing, using a single tri-axial accelerometer. Methods: 97 participants were recruited, forming four groups: cognitive impairment due to Alzheimer’s disease (AD; n=31), dementia with Lewy bodies (DLB; n=26), Parkinson’s disease dementia (PDD; n=13); and normal ageing controls (n=27). Participants were asked to stand still for two minutes in a standardised position with eyes open while wearing a single tri-axial accelerometer on their lower back. Seven balance characteristics were derived, including Jerk (combined, medio-lateral, anterior-posterior), Root Mean Square (RMS; combined, medio-lateral, anterior-posterior), and Ellipsis. Mann Whitney-U tests identified balance differences between groups. Receiver operating characteristics and area under the curve (AUC) determined overall accuracy of selected balance characteristics. Results: The PDD group demonstrated higher RMS (combined (p =.001), medio-lateral (p=.005), anterior-posterior (p=.001)) and ellipsis scores (p < .002) than AD (AUC: .71-.82). The PDD group also demonstrated significantly impaired balance across all characteristics (p≤.001) compared to controls (AUC: .79-.83). Balance differences were not significant between PDD and DLB (AUC: .69-.74), DLB and AD (AUC: .50-.65), DLB and controls (AUC: .62-.68) or AD and controls (AUC: .55-.67) following Bonferroni correction. Discussion: Although feasible and quick to conduct, key findings suggest that an accelerometer-based balance during quiet standing does not differentiate dementia disease subtypes accurately. Assessments that challenge balance more, such as gait or standing with as eyes-closed, may prove more effective to support differential diagnosis.